Extremal points without compactness in L1(μ) - Anna Martellotti (Journal of Function Spaces and Applications)
We investigate the existence of extremal points and the Krein-MIlman representation A=co⁡̅Ext⁡A of bounded convex subsets of L1(μ) which are only closed with respect to the topology of μ-a.e. convergence.